Bleeding disorders in the tribe: result of consanguineous in breeding - Borhany, Munira (BioMed Central, 2010)
OBJECTIVE: To determine the frequency and clinical features of bleeding disorders in the tribe as a result of consanguineous marriages. DESIGN: Cross Sectional Study INTRODUCTION: Countries in which consanguinity is a normal practice, these rare autosomal recessive disorders run in close families and tribes. Here we describe a family, living in village Ali Murad Chandio, District Badin, labeled as haemophilia. PATIENTS & METHODS: Our team visited the village & developed the pedigree of the whole extended family, up to seven generations. Performa was filled by incorporating patients, family history of bleeding, signs & symptoms, and bleeding from any site. From them 144 individuals were screened with CBC, bleeding time, platelet aggregation studies & RiCoF. While for PT, APTT, VWF assay and Factor VIII assay, samples were kept frozen at -70 degrees C until tested. RESULTS: The family tree of the seven generations comprises of 533 individuals, 63 subjects died over a period of 20 years and 470 were alive. Out of all those 144 subjects were selected on the basis of the bleeding history. Among them 98(68.1%) were diagnosed to have a bleeding disorder; 44.9% patients were male and 55.1% patients were female. Median age of all the patients was 20.81, range (4 months- 80 yrs). The results of bleeding have shown that majority had gum bleeding, epistaxis and menorrhagia. Most common bleeding disorder was Von Willebrand disease and Platelet functional disorders. CONCLUSION: Consanguineous marriages keep all the beneficial and adversely affecting recessive genes within the family; in homozygous states. These genes express themselves and result in life threatening diseases. Awareness, education & genetic counseling will be needed to prevent the spread of such common occurrence of these bleeding disorders in the community.